Central Asia in the era of sovereignty the return of Tamerlane? - Burghart, Daniel L.; Sabonis-Helf, Theresa (Contemporary Central Asia (Lanham, Md.), 2018)
"This collection provides a broad analysis of social, political, economic, and security issues in contemporary Central Asia. In particular, the contributors highlight the differences and similarities among the region's states in how they have consolidated statehood since the collapse of the Soviet Union"--